57.9k views
4 votes
How to solve?
(x-3) (x+4) = x^2 + 4

2 Answers

4 votes
First, you have to multiply (x -3) times (x+4), which is x^2 + 4x - 3x -12 (because x times x +4 = x^2 + 4x, and -3 times x + 4 =  -3x -12). So now we have the equation x^2 + 4x - 3x -12 = x^2 + 4. Subtracting x^2 from both sides, we get 4x - 3x - 12 = 4. Now we subtract 4 from both sides and get 4x - 3x - 12 -4. If we add/subtract the like terms, we get x - 16. Adding 16 to both sides, we get x = 16. I hope this helps! :D
User Spouk
by
5.9k points
4 votes
first step, expand the left side (multiply together) (apply FOIL/distribution property)

2nd step, solve so that one side is zero, by adding/subtracting like terms

3rd step, solve for x
User VolkerK
by
5.6k points